Multiple Quality Parameters for Image Quality assessment (International Journal of Engineering and Computer Science, 2014)
There has been an attention is boosted towards extending the IQA which follows two stage structures; in first stage, the reference and compressed images are taken as input by local quality measurement and the second stage advances it to the pooling stage and provides quality score. In the initial time, various methods such as MSE, PSNR, Correlation and Entropy are most used for the quality evaluation but this does not recommend any structural information of images. To diminish this restriction and offer structural information, initiative behind organizing this paper to accomplish most excellent overall performance is to progress the pictographic quality by merging information content weighting with structural similarity measurement.